Pemberdayaan Masyarakat Melalui Edukasi Pemanfaatan Limbah Cair Tempe Menjadi Biogas di Desa Habaring Hurung - Zahrotun Nafisah; Sudarman Rahman; Zimon Pereiz; Meiyanti Ratna Kumalasari - (Universitas Islam Indonesia, 2024)
The level of understanding among tempeh producers in Habaring Hurung Village on waste treatment remains significantly limited. Liquid waste from production is directly discharged into water bodies and causes various environmental problems. Consequently, a program was implemented to provide knowledge regarding suitable technology for effectively managing tempeh liquid waste to produce environmentally sustainable biogas. This initiative occurred in Habaring Hurung Village in the Bukit Batu District of Palangka Raya City. The community empowerment activity begins with a careful preparation process, followed by collaborative efforts with partners, the assembly of biogas reactors, and socialization initiatives, and concludes with an evaluation phase. The findings derived from this project indicate that the Habaring Hurung Village community has demonstrated proficiency in constructing biogas reactors. Moreover, there has been an obvious improvement in the community's understanding of liquid waste utilization and environmental management.